Smile esthetic evaluation of mucogingival reconstructive surgery - Rotundo, Roberto; Genzano, Luigi; Nieri, Michele; Covani, Ugo; Peñarrocha-Oltra, David; Peñarrocha-Diago, Miguel (Odontology, 2021)
[Abstract] To assess the difference in smile esthetic impact of Coronally Advanced Flap (CAF) with or without the adjunct of a collagen matrix (CMX) used as root coverage procedures. Subjects with esthetic demands showing multiple upper gingival recessions of at least 2 mm, without interproximal attachment loss and cervical abrasion no more than 1 mm were recruited and randomized to CAF plus CMX or CAF alone. The Smile Esthetic Index (SEI) was adopted to quantify the quality of the smile recorded at baseline and 12 months after treatment for each treatment group. In addition, between group difference in the SEI was calculated. 24 Patients were treated and analysed. At baseline, mean gingival recession depths were 2.3 +- 0.7 mm for Test group and 2.6 +- 1.0 mm for Control group. After 1 year, the residual recession depth was 0.3 +- 0.4 mm in the CAF + CMX group and 0.6 +- 0.3 mm in the control group. The SEI at baseline was 8.1 +- 1.0 and 7.9 +- 0.7 for Test and Control group, respectively. The between groups difference at 12 months in SEI was 0.4 (95% C.I. -0.0 to 0.8, P = 0.0697). Twelve months after treatment, CAF + CMX provided a similar SEI compared to CAF alone and the adjunct of a collagen matrix did not show a different impact on the smile esthetic appearance.